Implementation and Evaluation of a Barcode-Based Motorcycle Spare Parts Stock Opname Application Using the Spiral Model - Indrayana, Didik; Prajoko, Prajoko (Politeknik Negeri Lhokseumawe, 2025)
Using a barcode-based application, this study aims to make the stock-taking process for motorcycle spare parts at PT XYZ faster and more accurate. The traditional method currently used, which involves manual recording on paper and re-entering data into spreadsheets, takes up to two weeks and is prone to human error. This research proposes a solution by developing an application that enables real-time data input, inter-branch data synchronization, and automatic report generation. The system development employs the Spiral model with a quantitative approach to measure improvements in efficiency and accuracy. The research was conducted over six months (September 2024-February 2025) at PT XYZ, covering the head office and 14 branches in Sukabumi City. Data were collected through observation, interviews, and analysis of previous stok opname documents. The results show that the application implementation reduced the processing time from two weeks to one day and significantly decreased error rates. These findings demonstrate that the barcode-based application can enhance the accuracy and efficiency of the stok opname process, providing an important contribution to optimizing inventory management of spare parts in the automotive industry.